2015
DOI: 10.1017/s1041610215000733
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hemoglobin levels, cerebral small-vessel disease, and cortical atrophy: among cognitively normal elderly women and men

Abstract: Our findings suggested that decreased hemoglobin levels affected cortical atrophy, but not increased CSVD, among women, although the association is modest. Given the paucity of modifiable risk factors for age-related cognitive decline, our results have important public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Many previous studies linking anemia and dementia have suggested various mechanisms, unfortunately none of which are fully established, including the following: Chronic brain hypoxia related to anemia may partially contribute to cognitive function decline through accelerating the accumulation of amyloid-β [ 27 ]. Anemia has shown an association with the progression of white matter hyperintensity [ 28 ] and cerebral cortical atrophy [ 29 ]. Iron deficiency in the brain may affect its neurotransmitter metabolism and function through interference with rate-limiting enzymes that are dependent on iron [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies linking anemia and dementia have suggested various mechanisms, unfortunately none of which are fully established, including the following: Chronic brain hypoxia related to anemia may partially contribute to cognitive function decline through accelerating the accumulation of amyloid-β [ 27 ]. Anemia has shown an association with the progression of white matter hyperintensity [ 28 ] and cerebral cortical atrophy [ 29 ]. Iron deficiency in the brain may affect its neurotransmitter metabolism and function through interference with rate-limiting enzymes that are dependent on iron [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia has shown an association with the progression of white matter hyperintensity [ 28 ] and cerebral cortical atrophy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the link between decreased haemoglobin levels and neuroimaging markers of CSVD, and the results remain controversial. One study has reported a link between anaemia and white matter hyperintensity progression among patients with hypertension [ 13 ], whereas a recent study failed to find an association with white matter hyperintensity volume in a large community-based study [ 14 ]. The latter study also did not find any significant link with lacunes and cerebral microbleeds [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data has shown that anaemia is associated with a chronic hypoxic state that contributes to increased cerebrovascular burden, resulting in increased white matter hyperintensity volume [ 11 13 ]. However, a recent study showed no association between lower haemoglobin levels and the presence or progression of CSVD [ 14 ]. Moreover, the association of haemoglobin with cerebral microbleeds, and cortical cerebral microinfarcts remain unstudied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation